Can Ethical Behaviour Really Exist in Business - Bartlett, Andrew (Journal of business ethics, 2000)
Our soft survey reveals that the assumption underlying much of the business ethics literature -- that the conduct of business can and ought to support the social good -- is not accepted within the workplace. This paper considers an apparent dichotomy, with companies investing in ethical programs whose worth their employees and managers question. We examine the relationship between work, bureaucracy and "the market" and conclude that employees often question the existence of business ethics because there is no good and bad between which to choose. The choice is between success and failure. A common view of success and the "good life" is one determined by hard work in a well-organised company operating in a free market. Analysing the three aspects of this view (the free market, hard work, bureaucracy) we suggest these are mere fictions. A major problem we identify in business is that organisations are designed as profit making mechanisms and have no interest in the good of society. The challenge is to convince such organisations that a direct benefit accrues to them through their own ethical behaviour. In order to do this organisations must first be shown the importance of long termism. Executives, managers and other employees can be expected to attain high ethical standards only when they feel they are a integral part of an organisation and the organisation itself respects those standards. One of the keys to unravelling the undesirable situation of a perceived absence of ethics in business is in encouraging a greater identity community, company and workforce. We provide some examples of ways companies can meet the challenge of encouraging more ethical, long-sighted behaviour. In addition, we highlight ways in which the expectations of the organisations of the organisation can be communicated more strongly through corporate structures that foster ethical action that benefits the long term interests of the individual and the organisation. Overall implementing a successful ethical program is shown to parallel that of the implementation of a quality program.